1990
DOI: 10.2527/1990.68113624x
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and carcass composition of lambs infused for 28 days with a growth hormone-releasing factor analogue.

Abstract: A human growth hormone-releasing factor analogue, [DesNH2Tyr1,D-Ala2,Ala15]hGRF(1-29)NH2 (GRF-A), was infused s.c. into lambs for 28 d to determine its effects on growth performance and carcass composition. Twenty crossbred wethers weighing 47.0 +/- .5 kg were implanted with 7-d osmotic minipumps at weekly intervals. Minipumps contained either vehicle (dimethyl sulfoxide:H2O, 1:1) or GRF-A, released at a rate of 208 pmol (or .7 micrograms).h-1.kg-1. During the infusion period, plasma GH levels were increased (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
4
3
1
Order By: Relevance
“…Pelvic and internal fat tissue did not change in bST group. This finding is in agreement with previous studies (McLaughlin et al 1994;Godfredson et al 1990;Johnsson et al 1986;Muir et al 1983). Analysis of the carcasses showed some carcass components were affected by bST treatment.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Pelvic and internal fat tissue did not change in bST group. This finding is in agreement with previous studies (McLaughlin et al 1994;Godfredson et al 1990;Johnsson et al 1986;Muir et al 1983). Analysis of the carcasses showed some carcass components were affected by bST treatment.…”
Section: Discussionsupporting
confidence: 95%
“…There was no difference in spleen weight between treatment and control groups. Godfredson et al (1990) also reported that, growth hormone treatment did not change spleen weight in lambs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other authors (5,13) have described similar findings. The animals in our study and those used by them were in the active growth period in which the somatotrophic axis seems to be maximally stimulated (15) and thus difficult to be modified by exogenous GHRH.…”
Section: Discussionsupporting
confidence: 75%
“…On the contrary, continuous GHRH infusion using slow release pellets or osmotic minipumps did not modify circulating GH levels. These data differed from those reported by other authors (13) in which an elevation in plasma GH levels after continuous GHRH administration was described. The infusion of a more potent GHRH analog than ours in GODFRED-SON's studies could explain their results.…”
Section: Discussioncontrasting
confidence: 57%